The components of arginine and methylarginine metabolism are indicative of altered kidney function in intrauterine growth-restricted neonates - Kleinebenne, Lina; Röhrig, Waldemar; Ebach, Fabian; Reutter, Heiko Martin; Pankraz, Alexander; Heuchel, Katharina Monika; Müller, Andreas; Hilger, Alina (Journal of Hypertension, 2024)
Background: Intrauterine fetal growth restriction (IUGR) affects up to 10% of all pregnancies. Severe IUGR is associated with impaired kidney development, reduced nephron endowment, and chronic kidney disease later in life. Currently, no early predictive biomarker exists for detecting altered kidney function in neonates with IUGR. Because nephrons produce key enzymes for the metabolism of arginine and methylarginine components, we quantified and compared the concentrations of arginine and methylarginine metabolites between IUGR and non-IUGR neonates to identify potential biomarkers for the early detection of altered kidney function in IUGR neonates. Methods: Seventy-one IUGR and 123 non IUGR neonates were examined. Serum and Urine samples were obtained between 30 h and 5 days of life and between 5 and 70 days of life. Serum concentrations of creatinine, urea, symmetric and asymmetric-dimethylarginine metabolites (SDGV, SDMA, ADGV, and ADMA), guanidino-2-oxo-caproic acid (GOCA), citrulline, homocitrulline, arginine, and homoarginine were quantified using LC-MS/MS and standard clinical laboratory methods. Datasets were compared by Mann - Whitney - Wilcoxon or Chi-square tests for continuous and discrete parameters. P values were corrected for multiple comparisons using the Bonferroni method. Results: After Bonferroni correction, we found that serum creatinine, urea, SDGV, ADGV, and GOCA levels were significantly lower in neonates with IUGR. Consequently, the ratios of SDGV/SDMA, ADGV/ADMA, and GOCA/homoarginine were significantly lower in IUGR neonates. Conclusion: Our study suggests that arginine and methylarginine are possible early biomarkers for detecting altered kidney function in IUGR neonates.
CRIS-Team Scopus Importer:2024-09-06
Keywords: ADMA; AGXT2; arginine metabolites; glomerular filtration rate; homoarginine; IUGR; kidney function; SDMA